Stability Analysis of a Landslide Scarp by Means of Virtual Outcrops: The Mt. Peron Niche Area (Masiere di Vedana Rock Avalanche, Eastern Southern Alps) - Livio, Franz A.; Bovo, Francesco; Gabrieli, Fabio; Gambillara, Roberto; Rossato, Sandro; Martin, Silvana; Michetti, Alessandro M. (Frontiers in Earth Science, 2022)
We investigated the Mt. Peron niche area of the Masiere di Vedana rock avalanche (BL), one of the major mass movements that affected the Eastern Southern Alps in historical times. So far, a geomechanical characterization and a stability analysis of the niche area, where potential rockfalls sources are present, is lacking. The Mt. Peron niche area is a rocky cliff almost inaccessible to field-based measurements. In order to overcome this issue, we performed a geo-structural characterization of a sector of the cliff by means of a UAV-based photogrammetric survey. From the virtual outcrop, we extracted the orientation of 159 fractures that were divided into sets based on a K-means clustering algorithm and field-checked with some measurements collected along a rappelling descent route, down to the cliff. Finally, with the aim of evaluating the stability of the volume under investigation, we performed a stability analysis of three rock pillars included in our survey, by means of a distinct element numerical simulation. Our results indicate that two out of the three pillars are characterized by a stable state, under the simulation assumptions, whereas the third is close to failure and for this reason, its condition needs further investigation.